2015
DOI: 10.1007/s10552-015-0680-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and mammographic density in Mexican women

Abstract: Background Bone mineral density (BMD) is a putative marker for lifetime exposure to estrogen. Studies that have explored whether BMD is a determinant of mammographic density (MD) have observed inconsistent results. Therefore, we examined this potential association in a sample of women (N=1,516) from the clinical sub-cohort in the Mexican Teachers’ Cohort (N=115,315). Methods We used multivariable linear regression to assess the association between quartiles of BMD and percent MD, as well as total dense and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…45 In addition, a recently published study reported no association overall, but a positive association between BMD and percent mammographic density among obese women, and an inverse association among leaner women. 34 This suggests a complex association. Nevertheless, studies evaluating the association of BMD with percent mammographic density have not stratified their analyses by BMI, except for one conducted among Kuwaiti women.…”
Section: Bmi Bmd and Mammographic Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…45 In addition, a recently published study reported no association overall, but a positive association between BMD and percent mammographic density among obese women, and an inverse association among leaner women. 34 This suggests a complex association. Nevertheless, studies evaluating the association of BMD with percent mammographic density have not stratified their analyses by BMI, except for one conducted among Kuwaiti women.…”
Section: Bmi Bmd and Mammographic Densitymentioning
confidence: 99%
“…Only three studies have investigated the association of BMD at other sites, including ribs, arms, leg, and whole body, with mammographic density 28,33,34 and two studies reported no associations overall. However, Sung et al observed a positive association of BMD at the legs with mammographic density among premenopausal women (b = 0.59, p < 0.05) 33 ( Table 3).…”
Section: Bmd At the Hipmentioning
confidence: 99%
See 1 more Smart Citation